Recognition as Evidence that Determines the Validity of the Sale and Purchase of Land and Buildings (Case Study: Case No. 1298 K/PDT/2022) - Pangarso Wicaksono, Adhiputro; Saptanti, Noor (Universitas PGRI Madiun, 2023)
Disputes can occur because of misunderstandings, differences of opinion, defense of interests, rights and obligations that are not fulfilled, and one party feels disadvantaged. One of the evidence in the dispute or case of the validity of the sale and purchase of land and buildings is recognition. This study aims to find out and analyze the application of the Civil Procedure Proof System, especially evidence of recognition. This research is a normative study using a case approach and deductive analysis. The legal material used is primary legal material in the form of a court decision and relevant laws and regulations. The results showed that in the case of the Plaintiff as the seller of land and the building as mentioned in the sale and purchase deed denied the sale of land and his building, but because in the lawsuit the Plaintiff admitted that he had received money from the buyer (Defendant I), the sale and purchase was considered valid with all legal consequences